2005
DOI: 10.1074/jbc.m504260200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase Activity of Alkaline Phosphatase in ATP-initiated Ca2+ and Phosphate Deposition in Isolated Chicken Matrix Vesicles

Abstract: Inorganic pyrophosphate is a potent inhibitor of bone mineralization by preventing the seeding of calcium-phosphate complexes. Plasma cell membrane glycoprotein-1 and tissue nonspecific alkaline phosphatase were reported to be antagonistic regulators of mineralization toward inorganic pyrophosphate formation (by plasma cell membrane glycoprotein-1) and degradation (by tissue nonspecific alkaline phosphatase) under physiological conditions. In addition, they possess broad overlapping enzymatic functions. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 63 publications
3
38
0
6
Order By: Relevance
“…In contrast, the residual Ca solids displayed a very strong band at 1036 cm -1 , with surrounding weaker bands at 962 and 1093 cm -1 . The FTIR spectral pattern for the Ca residual was similar to that for hydroxyapatite itself and agrees with literature reports (Zhang et al 2005). The appearance of bands at 1417 and 1457 cm -1 in the FTIR spectrum of the Ca residual suggests that there might be some other, as yet identified, product present (these bands were not evident in the hydroxyapatite spectrum).…”
Section: 3supporting
confidence: 77%
“…In contrast, the residual Ca solids displayed a very strong band at 1036 cm -1 , with surrounding weaker bands at 962 and 1093 cm -1 . The FTIR spectral pattern for the Ca residual was similar to that for hydroxyapatite itself and agrees with literature reports (Zhang et al 2005). The appearance of bands at 1417 and 1457 cm -1 in the FTIR spectrum of the Ca residual suggests that there might be some other, as yet identified, product present (these bands were not evident in the hydroxyapatite spectrum).…”
Section: 3supporting
confidence: 77%
“…NPP and AP are evolutionarily related members of the AP superfamily that have evolved to catalyze different reactions with remarkable specificity despite having very similar active sites. There are also members of the AP superfamily that appear to have nearly equivalent activities for phosphate monoester and diester hydrolysis (65). These enzymes may represent intermediate states along the evolutionary path from a specific phosphate monoesterase to a diesterase or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the enzymatic characteristics observed in HeLa cells in our study indicated that PLAP is the most prominent isoform in these cells. Phosphodiesterase activity has been reported for TNAP, but not for PLAP (26,27). Importantly, in this study, phosphodiesterase activity using cAMP as substrate was not detected in HeLa cells (data not shown).…”
Section: Figure 6 Expression and Isoform-specific Inhibition Of Ap Imentioning
confidence: 54%